2011
DOI: 10.3758/s13415-011-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

The reward of a good joke: neural correlates of viewing dynamic displays of stand-up comedy

Abstract: Humor is enjoyable, yet few studies to date have reported that humor engages brain regions involved in reward processing (i.e., the mesolimbic reward system). Even fewer have investigated socially relevant, dynamic displays of real actors telling jokes. Instead, many studies have focused on responses to static cartoons or written jokes in isolation. In the present investigation, we used functional magnetic resonance imaging (fMRI) to examine brain activation in response to video clips of comedians performing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 29 publications
6
42
0
2
Order By: Relevance
“…This system constitutes a network encompassing both cortical (e.g., medial temporal, prefrontal and orbitofrontal cortices) and subcortical areas, including midbrain structures (ventral tegmental area, substantia nigra) and the ventral striatum (nucleus accumbens, caudate, putamen) [52]. Data from the literature show that this system is activated during the processing of humorous stimuli such as cartoons [26,53], comedy clips [54], and verbal jokes [29], and could be thus extended to ironic sentence listening.…”
Section: Discussionmentioning
confidence: 99%
“…This system constitutes a network encompassing both cortical (e.g., medial temporal, prefrontal and orbitofrontal cortices) and subcortical areas, including midbrain structures (ventral tegmental area, substantia nigra) and the ventral striatum (nucleus accumbens, caudate, putamen) [52]. Data from the literature show that this system is activated during the processing of humorous stimuli such as cartoons [26,53], comedy clips [54], and verbal jokes [29], and could be thus extended to ironic sentence listening.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies have indicated that both the lentiform nucleus and the midbrain are implicated in positive reward prediction errors (D'Ardenne et al, 2008;O'Doherty et al, 2006), as well as self-reported happiness and monetary rewards (Knutson and Cooper, 2005;Knutson et al, 2001) and are activated during the detection of attractive faces (Cloutier et al, 2008) and in addiction (Reuter et al, 2005). Studies regarding humor comprehension have indicated that subcortical regions, including the amygdala, nucleus accumbens, midbrain (VTA), and hypothalamus, contribute to the aspect of humor appreciation (Franklin and Adams, 2011;Azim et al, 2005;Mobbs et al, 2003Mobbs et al, , 2005Moran et al, 2004;Schwartz et al, 2008;Vrticka et al, 2013a).…”
Section: Activation Of the Mesolimbic Reward Systemmentioning
confidence: 98%
“…Over the past decade, many neuroimaging studies have examined the neural substrates involved in humor comprehension (Bekinschtein et al, 2011;Chan et al, 2012aChan et al, , 2012bFranklin and Adams, 2011;Dolan, 2001, 2007;Marinkovic et al, 2011;Mobbs et al, 2003Mobbs et al, , 2005Moran et al, 2004;Neely et al, 2012;Rapp et al, 2008;Samson et al, 2009Samson et al, , 2008Vrticka et al, 2013aVrticka et al, , 2013cWatson et al, 2007;Wild et al, 2006). These studies can be classified into two main groups based on the stimulus modalities used in the experiments: visual and verbal.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all insight experiences are funny. Previous imaging studies of humor have contrasted humorous stimuli with the same stimuli without the humorous element (e.g., Mobbs et al 2003;Moran et al 2004;Bartolo et al 2006;Kohn et al 2011), and/or compared different kinds of humor (e.g., Goel and Dolan 2001;Watson et al 2007;Samson et al 2008Samson et al , 2009Franklin and Adams 2011). Unfortunately, a comparison among subtypes of humor necessarily ignores the regions involved in all humor, and a comparison of humorous stimuli to the same stimuli with the humorous element removed may be too broad, as controls lack the element of discovery.…”
Section: Introductionmentioning
confidence: 97%